THE DETERMINATION OF THE OPTIMAL PARAMETERS OF THE BEARING ALLOYS MICROSTRUCTURE IN CONTACT FRICTION AREA - Kuzin, M. O.; Meshcheryakova, T. M. (Science and Transport Progress, 2009)
The possibility of using the simulation structure models and variation models of mechanics is shown for finding quantity and size of antifriction alloy phase with raised wear resistance. The numerical realization of models displays that the optimal value of structure parameters of babbit B16 is 56 % of hardening phase SnSb with average size of 47 mkm.